2018
DOI: 10.22159/ijap.2018v10i1.21584
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Characterization of Sustained Release Matrix Tablets of Ivabradine Using 32 Full Factorial Design

Abstract: Objective: Ivabradine (IB) is anti-Ischemic drug and used for the symptomatic management of stable angina pectoris. IB acts by reducing the heart rate in a mechanism different from beta blockers and calcium channel blockers, two commonly prescribed anti-anginal drugs. IB has a short biological half-life and the dose of 5/7.5 mg twice a day. In this present study, an attempt has been made to prepare sustained release tablet of IB to achieve the desired drug release. Methods:The sustained release polymers, hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 3 publications
0
13
0
Order By: Relevance
“…The underlying goal and end-game for all ADME studies are to better understand a compound's metabolite-mediated toxicity and safety profile to make a concrete decision on whether the compound can progress to late-stage preclinical and clinical studies to enable filing for an investigational new drug, new drug agreement, or a biologics licensing agreement. ADME studies can be used in molecular docking, pharmacophore modeling, de novo designing, fragment-based screening, to find structure-activity relationships [25,26]. Transporters play an important role in the ADME of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying goal and end-game for all ADME studies are to better understand a compound's metabolite-mediated toxicity and safety profile to make a concrete decision on whether the compound can progress to late-stage preclinical and clinical studies to enable filing for an investigational new drug, new drug agreement, or a biologics licensing agreement. ADME studies can be used in molecular docking, pharmacophore modeling, de novo designing, fragment-based screening, to find structure-activity relationships [25,26]. Transporters play an important role in the ADME of drugs.…”
Section: Discussionmentioning
confidence: 99%
“…Here in equation 3, b 2 value is more negative than b 1 which indicated that EC had more release retardant effect compare to the HPMC K100M at 1 h [ Figures 4 and 5]. [20] Regression analysis for the effect of X 1 and X 2 on in vitro drug release at 4 h […”
Section: Regression Analysis For the Effect Of X 1 And X 2 On In Vitrmentioning
confidence: 99%
“…A factor was considered to influence the response if the effects are significant (p<0.05). A positive value indicates a synergistic effect that favors optimization, while a negative sign represents an antagonistic effect or inverse effect of the factor on the selected response [13]. When we study the optimization of formulation for 100 mg constant drug amount considering 70% CPR at 8 h and 100% Drug Entrapment Efficiency it was observed that 200 mg total polymer, 30% gelatin wrt total polymer and 6 h oxidation reaction time is the predicted optimized formula for around 91% DEE and 72%CPR at 8 h. This prediction matches with the formulation No.…”
Section: Estimation Of Quantitative Effects Of Factorsmentioning
confidence: 99%